Three invasive insects alter Cycas micronesica leaf chemistry and predict changes in biogeochemical cycling - Marler, Thomas E. (Commun Integr Biol, 2016)
Leaf litter chemical traits were measured for Cycas micronesica plants in Guam following leaf herbivory by the scale Aulacaspis yasumatsui, the butterfly Chilades pandava caterpillar, or the leaf miner Erechthias sp. to determine the influence of the non-native pests on litter quality. Scale herbivory increased litter phenols above those of undamaged leaves but did not influence lignin or cellulose concentrations. Butterfly caterpillar herbivory increased litter phenols above and decreased litter lignin below those of undamaged leaves, but did not influence cellulose concentrations. Leaf miner herbivory increased litter lignin concentrations above those of undamaged leaves, but did not influence phenols or cellulose concentrations. Herbivory influenced 8 of 12 essential elements that were quantified. Herbivory by all 3 insects increased nitrogen and potassium litter concentrations and decreased calcium and iron litter concentrations when compared with undamaged litter. The responses were idiosyncratic among herbivores for the remaining essential elements. Stoichiometry among the chemical constituents indicated that herbivory increased litter quality and predicted more rapid biogeochemical cycling in Guam's ecosystems as a result of these 3 non-native insect invasions.